1980
DOI: 10.1071/ar9801129
|View full text |Cite
|
Sign up to set email alerts
|

Measurement in sheep of the quantity and composition of rumen digesta and of the fractional outflow rates of digesta constituents

Abstract: Knowledge of the fractional outflow rates of rumen digesta constituents is required for the quantitative prediction of rumen function. However, there are few data available for these parameters because of the problems associated with specific labelling of digesta constituents and with the need to ensure that samples are truly representative of rumen digesta. Methods are described here by which two markers can be used together to overcome the problem of representative sampling of the rumen, so eliminating the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

1983
1983
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 1 publication
1
67
0
2
Order By: Relevance
“…However, higher values have been reported in other in vivo experiments. Craig et al (1987) reported a proportion of 70 -80 % of SAM in the rumen of cows fed a 65 % alfalfa haylage diet, with values up to 90 % in animals fed all-roughage diets (Faichney, 1980). The lower values in our batch culture system compared with some of those observed in vivo could be due to the different experimental conditions.…”
Section: Discussionmentioning
confidence: 45%
“…However, higher values have been reported in other in vivo experiments. Craig et al (1987) reported a proportion of 70 -80 % of SAM in the rumen of cows fed a 65 % alfalfa haylage diet, with values up to 90 % in animals fed all-roughage diets (Faichney, 1980). The lower values in our batch culture system compared with some of those observed in vivo could be due to the different experimental conditions.…”
Section: Discussionmentioning
confidence: 45%
“…The quantity of bacteria adherent to ruminal digesta can be altered by the previously mentioned dietary alterations as well as the presence of feed additives in the diet [76,77]. The impact of changing a component of the diet on ruminal fermentation has been of interest to many researchers.…”
Section: Microbial Fermentation In the Rumenmentioning
confidence: 99%
“…Although there is little information about the contribution of SAB and LAB to total bacterial flow, the relative proportion of SAB and LAB in the rumen can be affected by dietary factors. Indeed, Faichney (1980) reported that the proportion of SAB reached 90% in sheep fed forage only whereas it declined to 50% for steers fed equal proportions of forage and concentrate (Merry and McAllan, 1983). Hence, variation in relative proportions of SAB and LAB could largely influence estimates of rumen microbial synthesis when either SAB or LAB marker:N ratios are used for calculations.…”
Section: Introductionmentioning
confidence: 99%